Using business English as a lingua franca for written and spoken communication : challenges encountered by Thai human resources professionals in an American multinational company - Krich Rajprasit,; Janista Sirisuksakulchai,; Kanyanut Srimontra,; Nutcha Pitakpornsin,; Phatcharin Letakulkit,; Picharee Phaiboontham,; Soungkwan Dumrongruedee, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Unquestionably, English is a medium for international communication, particularly in multinational companies (MNCs). In this regard, professionals who work in MNCs, including human resources (HR), inevitably encounter challenges in using English in the workplace environment where people are from diverse linguistic and cultural backgrounds. This study attempts to examine how Thai HR professionals perceived the role of business English as the lingua franca (BELF) and how they faced the challenges in using English for workplace communication. This survey study employed a mixed-methods approach for data collection. A questionnaire survey and semi-structured interview were developed to collect the data. Thirty-nine Thai HR professionals at an American oil and gas subsidiary in the Bangkok metropolitan area were purposively selected. Data collected from both instruments were analysed using descriptive statistics and content analysis, respectively. Our data analysis demonstrates that most of the respondents had a positive attitude about using BELF in their organisation. However, it was necessary for them to be aware of their interactants’ diverse linguistic and cultural backgrounds and to effectively use BELF and avoid serious mistakes in their written and spoken communication. In summary, this study reveals that the Thai HR professionals understood the BELF concept and faced more difficulties in spoken communication tasks (e.g., press briefings and business negotiations) in comparison to written tasks. The findings can be beneficial for educators and HR trainers in terms of awareness of intercultural business communication and guidance for developing BELF-oriented courses for university students, graduates and HR professionals.